Two new species of Lasiopa (Diptera, Stratiomyidae) from Turkey - Üstüner, Turgay; Hasbenli̇ Abdullah (Zootaxa, 2014)
Two new species, Lasiopa aksarayiensis sp. n. and Lasiopa aktasii sp. n. are described from the Central Anatolian stepe in Turkey. All diagnostic characters are illustrated and possible relationships of both taxa are briefly discussed. The first record of Lasiopa pseudovillosa (Rozkošný, 1983) from Turkey is presented and additional Turkish localities of Lasiopa caucasica (Pleske, 1901) are recorded and an identification key to all the Palaearctic species of Lasiopa is given.